A Critical Review of the Book “Female Calligraphists of Iran, from Zainab Shahdad to Umme Salama” - Mostafa Rostami; Moeine Sadat Hejazi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Today, the debate on women-related issues has come to prominence as an international discourse. Discussing women’s issues as a large demographic group of the society can be conducive to promoting various social, cultural, economic, and political dimensions. Given the scant attention paid to the instrumental role of women in various aspects of social, family, economic, political, cultural, and artistic activities, the gap of such studies is particularly felt in countries such as Iran. In recent years, Iranian women have been struggling to achieve their proper status. The great potentials of women in diverse cultural and artistic fields of activities are not unknown to anyone. The book, “Female Calligraphists of Iran” by Tahereh Molamohammadi, is one of the first works attempting to recognize Iranian women and cultivate their potentials. The introduction of the character and works of the female calligraphists in the history of Islamic era in Iran is the major contribution of this seminal book. The present study aims to take a critical approach at “Female Calligraphists of Iran” through an analysis of its content.